International Human Rights Law and Practice in Latin America - Ellen L. Lutz and Kathryn Sikkink (My University, 2016)
Human rights practices in Latin America provide a lens through which to examine the relationship between international law and domestic politics. International human rights norms are expressed in numerous widely ratified treaties. Many of those norms also are embedded in customary international law. The number of binding human rights norms incorporated into international or regional law as well as the precision and delegation of those norms increased significantly between the mid- 1970s and the mid-1990s. In addition, in the 1970s and 1980s an internationalhuman rights advocacy network committed to documenting and spotlighting human rights violations,drafting and implementing internationalhuman rights standards, and pressuring governments to implement bilateral and multilateral human rights policies emerged.